A Systematic Study of Human Gait Analysis Using Machine Learning Approaches - Yadav, Ankita; Verma, Dipti (International Journal of Computer Sciences and Engineering, 2018)
The prime objective of this paper is to comprehend the human gait in biometric and biomedical applications. Human gait recognition is recognizing people from the manner in which they walk. It is identified with acquiring biometric data, for example, identity, gender, ethnicity and age from people walking patterns. Likewise, biomedical data can be acquired like individual's illness, body abnormality. In the walking process, the human body shows general periodic motion, particularly upper and lower limbs, which reflect the person's unique movement pattern. Contrasted with different biometrics modalities, gait can be acquired from distance and is hard to hide and camouflage. Gait has been topic in PC vision with extraordinary advancement accomplished in ongoing ten years. In this paper, we give a survey over state-of-art gait innovation; focus on different factors in gait methodology and ongoing advances in biomedical engineering.